Review of Hans Volker Wolf, Looi Wai Ling, Stefanie Pillai, and Adriana Phillip (eds), The Mousedeer and the Crocodiles: A Malaysian Folktale in 111 Languages - Amirdabbaghian, Amin; Wolf, Hans Volker (Department of English, Faculty of Arts and Social Sciences, University of Malaya, 2018)
Hans Volker Wolf, Looi Wai Ling, Stefanie Pillai, and Adriana Phillip (eds). The Mousedeer and the Crocodiles: A Malaysian Folktale in 111 Languages. Kuala Lumpur: University of Malaya Press, 2017. xxvi + 300 pp. ISBN: 978-983-100-941-3.